Effectiveness and influencing factors of online teaching among primary and secondary school teachers in China during the COVID-19: in depth interviews - Ma, Xiaofang (Frontiers in Psychology, 2023)
During COVID-19, online teaching was adopted in many countries and online teaching effectiveness attracted widespread attention. This study used in-depth interviews to explore the factors affecting online teaching efficacy of primary and secondary school teachers from teachers' perspectives, and used open coding, axial coding, and selective coding to analyze and organize the interview materials. Five thematic elements were finally derived, namely acceptance, professionalism, interactivity, instructional leadership and support, and home-school collaboration. From the teacher's perspective, acceptance, professionalism, and interactivity are closely related to the individual teacher, while instructional leadership and support, and home-school collaboration are two important external elements. This study explored the influencing factors of teaching effectiveness in different contexts, enriched the theory of teaching effectiveness, and provided practical support for the future development of online teaching.